Efektivitas Murrotal Al – Quran terhadap Durasi Tidur pada Bayi Usia 6-12 Bulan - Sri Ayu Akuba; Fidya Hiola; Fifi Ishak; Sri Mulyaningsih (STIKes Hamzar, 2026)
Sleep duratio in toddlers is a factor that influences infant growth. To support good sleep duration, Murrotal Al-Quran treatment is necessary as a non-pharmacological therapy. This study aims to determine the effectiveness of Al-Quran murrotal therapy on sleep duration in infants aged 6-12 months in the Kabila Community Health Center Work Area. The research method used was a quasi-non-equivalent experiment with a control group pre-post test design approach. The study sample consisted of 32 individuals divided into two groups: an intervention group and a control group of 16 individuals each. Sleep duration was measured using an observation sheet. The results showed that only one participant met the required sleep duration during the pre-test intervention, and 12 participants met the required sleep duration during the post-test intervention. The statistical test showed a p-value of 0.001 (p<0.005), indicating the effectiveness of Quran recitation therapy on sleep duration in infants aged 6-12 months. The conclusion of this study is that Quran recitation therapy is effective on sleep duration in infants aged 6-12 months.